Relación entre el gasto real promedio per cápita mensual y los alimentos consumidos dentro del hogar en el Perú periodo 2019 – 2023 - Del Aguila Panduro, Ludwing Frank (2025)
The National Institute of Statistics and Informatics (INEI) quantifies the well being of residents using monetary aspects such as the average real monthly expenditure per capita, making it necessary to incorporate qualitative aspects related to people's standard of living and the satisfaction of basic needs. Therefore, this masterful research was developed to demonstrate the relationship between average expenditure and the resources dedicated to the purchase of food for consumption within the home, evaluated in the period 2019 - 2023. This study is of a Quantitative-Correlational type, and has a Non-experimental design. The study concludes by demonstrating the direct association between average expenditure and expenditure on the item Food Consumed Within the Home in the period 2019 - 2023, confirmed by the value of the Correlation Coefficient, which reached r = 0.970491033; and the Coefficient of Determination, which was R2 = 0.941852845. The average real expenditure per person on a monthly basis was concentrated on Food Consumed at Home (30.67%), which shows that a large part of the population does this because they do not have enough money to eat at restaurants or to save money to invest in other items. The natural region of the country with the highest real expenditure is the Coast, at S/. 986.00. The urban area has the highest average expenditure, at S/. 962.00.